Administração de bibliotecas em instituições privadas de ensino superior: uma abordagem discursiva a partir das novas demandas de acesso e uso da informação - Silva, Fátima Santana da (2013)
Based on the Theory of Communicative Act of Jugen Habermas this research seeks to drive administrative elements to libraries at private institutions of higher education in order to promote contemporary administration, taking into account the stakeholders views and expectations of these services. Focuses its foundations on the interrelations between Information Science and Management Science, which uses concepts of Discursive Administration, in order to furnish a dialogical perspective in the construction of new ways of working. From a case study in a private institution in Rio de Janeiro, and the literature review, identify aspects that can be taken as keys to the dialogue among the actors involved: INEP / MEC and its implicit reasons for serving higher education, taken from its assessment tools; librarians; and academic community, users (professors and students). These aspects provide support for professional practices reconfiguration in managing libraries of private higher education. The research result indicates a weakness in the administrative perspective of libraries and provides elements that can be used to reflection and starting points for a Discursive Management in Libraries Private Institutions of Higher Education